Management of Penile Defects: A Review - Guizhong, Li; Feng, He; Guangling, Huang; Libo, Man; Kun, Liu; Yuming, Shen (Journal of Reconstructive Microsurgery, 2012)
Penile amputation is a rare injury. Although, in principle, penile replantation can be performed using a variety of methods, few, if any, standardized procedures exist to deal with this medical emergency. The value of the various microsurgical techniques for replantation of the penis remains uncertain. This article provides a review of the management of penile defects and complications.
Keywords: penis; amputation; trauma; replantation